2010
DOI: 10.1002/app.32354
|View full text |Cite
|
Sign up to set email alerts
|

Structural, mechanical and thermal studies of double‐molded isotactic polypropylene nanocomposites with multiwalled carbon nanotubes

Abstract: Nanocomposites of isotactic polypropylene (iPP) and multiwalled carbon nanotubes (MWCNTs) with various contents of MWCNTs were fabricated by double molding techniques. X-ray diffraction measurements reveal a development of a-crystal with lamellar stacks having a long period of 150 Å in the neat iPP that increases to 165 Å in 2 wt % MWCNTs-loaded composites, indicating that MWCNTs enhance crystallization of iPP as a nucleating factor. Mechanical properties, such as tensile strength, flexural strength, Young's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Of organic fillers, carbon black (CB) have gained much attention in fabrication of polymeric composites, because CB reinforced composites are being exploited in many industrial and domestic appliances including self-regulating heating elements, current switching, fluid sensor, thermal controller, capacitors and electromagnetic interference shielding . However, research works found on filler reinforced polymer composites are mostly based on isotactic polypropylene (Akinci 2009, Mina et al 2010, though a few research works on filler loaded PE composites have been published (Ulutan et al 2000, Yuan et al 2003, Dang et al 2003, Luyt et al 2006. In addition, homogeneous dispersion of fillers in polymer matrix by melt blending has also been a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Of organic fillers, carbon black (CB) have gained much attention in fabrication of polymeric composites, because CB reinforced composites are being exploited in many industrial and domestic appliances including self-regulating heating elements, current switching, fluid sensor, thermal controller, capacitors and electromagnetic interference shielding . However, research works found on filler reinforced polymer composites are mostly based on isotactic polypropylene (Akinci 2009, Mina et al 2010, though a few research works on filler loaded PE composites have been published (Ulutan et al 2000, Yuan et al 2003, Dang et al 2003, Luyt et al 2006. In addition, homogeneous dispersion of fillers in polymer matrix by melt blending has also been a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the predictions of modulus by the developed model and the experimental data for several samples including polypropylene (PP)/multi‐walled CNTs (MWCNT) from, PP/MWCNT from, poly (vinyl alcohol) (PVA)/MWCNT from and poly (butylene terephthalate) (PBT)/single‐walled CNTs (SWCNT) from . The predictions acceptably follow the experimental results of modulus at all filler concentrations.…”
Section: Resultsmentioning
confidence: 53%
“…Therefore, the developed model based on Takayanagi can successfully predict the modulus of polymer/CNT nanocomposites assuming the roles of interphase and filler network. Also, the best levels of “ p ” as the effective factor for filler network are calculated as 1.4, 1.5, 5.25 and 6.5 for PP/MWCNT, PP/MWCNT, PVA/MWCNT and PBT/SWCNT samples, respectively. The values of “ p ” indicate that the different networks of nanoparticles form in these samples beside the interphase between polymer matrix and nanoparticles ( p > 0.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the onset of decomposition occurs earlier in APMWC than in any other sample. This difference in onset temperature can be explained by the following way, as reported elsewhere . The high thermal conductivity of MWCNTs may create localized high temperature in them as compared to PLA matrix.…”
Section: Resultsmentioning
confidence: 63%